Aquifer Identification Using the Schlumberger Vertical Electrical Sounding (VES) Method in Mulyojati Village, Metro Barat Subdistrict, Metro City - Difa Mutafawwiqoh; Anggara Putra Prasetyo; Acep Ruchimat; Budy Santoso (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
Groundwater is ideally expected to be available in a sustainable manner and managed based on adequate subsurface hydrogeological information. However, conditions in Mulyojati Village, Metro Barat Subdistrict, Metro City indicate a lack of site-specific data on aquifer characteristics, despite increasing groundwater demand driven by population growth and socio-economic activities. This limitation may lead to uncertainty in well drilling planning and groundwater utilization. Therefore, an effective preliminary exploration method is required to identify groundwater-bearing layers. This study applies the Vertical Electrical Sounding (VES) method using the Schlumberger configuration to investigate subsurface resistivity variations related to lithology and groundwater saturation. The urgency of this research arises from the absence of previous geophysical investigations in the area, particularly within the heterogeneous Qpt Formation, which is considered a potentially productive aquifer. The objective of this study is to characterize subsurface resistivity and delineate potential aquifer zones in Mulyojati Village. The results are expected to provide essential baseline information for groundwater development planning and support sustainable groundwater resource management in the Metro City area.